The Effect of Competence and Experience of Students Internship on the Readiness of Work - Iis Torisa Utami; Didik Hariyadi Raharjo (Wacana Journal of Social and Humanity Studies, 2020)
This research was aimed to know of the influence of competence and experience of internships on the work readiness of Secretarial Academy (ASTRI) Budi Luhur students. The population in this research was the students of ASTRI Budi Luhur Jakarta students were doing an internship program. The sample for this research taken using A purposive sampling method amounted to 41 students. Hypothesis testing was done by multiple regression using SPSS version 22 software. The results showed that were partial competency and experience of internships on the work readiness, with T count for competency variable (X1) of 4.700 with a significance level of 0.000 and T count for the internship experience variable (X2) of 2,533 with a significance level of 0.16 using a significance level of α = 0.05. and there was a simultaneous influence between competency variables and experience of internships on the work readiness with F count of 31.106 with a significance level of 0.000. this is supported by the grade point average (GPA) obtained by ASTRI Budi Luhur students is 3.92 or the title of praise, and the maximum score of the internship results obtained is 99 or grade A